National report for the International Conference on Population and Development (ICPD), 1994 (Development Planning Unit TortolaVG, 1994)
Provides a blueprint for development relative to population issues. Serves as a comprehensive reference for policies, strategies, plans, programmes and projects related to population and development. Outlines the National Plan of Action.
DC